Synergistic Effects of Chitosan and Fish Oil on Lipid Metabolism in Rats Fed a High-Fat and Low-Carbohydrate Diet - Liu, Shing-Hwa; Chang, Ting-Yu; Liu, Shih-Hou; Chiang, Meng-Tsan (Nutrients, 2024)
Background/Objectives: Although high-fat, low-carbohydrate diets are used for weight loss and type 2 diabetes management, their high-fat content may have negative effects. This study examines the effects of replacing cellulose with chitosan and part of the fat with fish oil in a high-fat, low-carbohydrate diet on lipid metabolism in rats. Methods: The experiment involved 35 six-week-old male SD rats, divided into five groups: normal control diet (ND), high-fat diet (HF), high-fat, low-carbohydrate diet (LC), LC with 5% chitosan (LC-CH), and LC with 5% chitosan and 5% fish oil (LC-CHF). Results: After 15 weeks, the HF group had the highest liver weight, and the LC group had the highest adipose tissue weight. The LC-CHF group showed significantly reduced body, liver, and adipose tissue weights, lower ALT, AST, TNF-α, and cholesterol levels, as well as improved liver enzyme activity and fat synthesis regulation. LC-CHF also promoted fat breakdown in adipose tissue, reducing adipocyte size. Conclusions: Our findings suggest the modified high-fat, low-carbohydrate diet with chitosan and fish oil improved obesity and fatty liver outcomes compared to a standard high-fat diet.